Analisis Kemampuan Berpikir Kritis Siswa SMP Kelas VIII MTs Hadil Ishlah Bilebante Berdasarkan Gaya Belajar - Hasmi Hidayati; Nyoman Sridana; Sri Subarinah; Ketut Sarjana (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe students' critical thinking skills based on learning styles with visual, auditory, and kinesthetic learning styles. This study was quantitative qualitative with descriptive method. The research subjects consisted of 8 students with each learning style at each level of critical thinking ability. Data collection in this study used tests to determine the level of students' critical thinking skills, questionnaires to determine student learning styles, and interviews. The test was carried out on the material of two-variable linear equations. The results of the tests and interviews were analyzed based on indicators of critical thinking skills: (1) interpretation, (2) analysis, (3) evaluation, (4) inference, and (5) explanation. The results showed that from 25 students there were 19 students in the category of high critical thinking skills with 6 visual, 5 auditory, and 8 kinesthetic students. 3 people with moderate critical thinking skills with 2 visual and 1 kinesthetic. 3 people with low critical thinking skills with 1 visual, 1 auditory, and 1 kinesthetic. Students with high category visual learning style can write interpretation, evaluation, inference, explanation, medium category can write interpretation, evaluation, inference, and low category can write interpretation. Students with a high category of auditory learning style can write inferences, low categories can write evaluations. Students with high category kinesthetic learning styles can write inference evaluations, medium and low categories can write evaluations.